The Idea of National Unity in the Georgian Historical Literature and Folk Sources - Arabuli, Amiran (Actual Problems of Kartvelology, 2019)
In the medieval Georgian chronicles and hagiographical texts the most prominent political and ecclesiastical figures, the supporters of the Georgian unity (King David the Builder, Queen Tamar, King Heraclius II…), are represented as executors of God’s desire. The same tendencies are impressively reflected in Georgian folk sources. The article discusses Georgian historical literature and oral sources which emphasize the idea of Georgian unity.